A call for disability health curricula in medical schools. Issue 12 (December 2022) - Ratakonda, Sanjana; Argersinger, Davis P.; Auchus, Gabriella C.; McGowan, Caroline; Ship, Hannah; Wang, David R.; McKee, Michael M.
Abstract : People with disabilities encounter significant health and health-care inequities yet disability health training in medical education remains inadequate. This Scientific Life article examines the need to integrate disability health education into medical school curricula and shares successful training examples that can serve as a framework for how to accomplish this.